(3cJGH aj GdgfOSIs - (3TeS GdOjf eMeO Hf GTQa GdSeQbfOj,J (B600 (3g` s ((3eMeO GdcJHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF HbOQ hHYO aEf GdgfOSI eY eJGfI eSGFdgG hhKGbg OdGFdgG HMjK dG jCJjgG GdHGWd Hjf jOjgG hdG ef NdagG s
(3BNQgG (B:s
(3hgPg GdCTcGd GdNeSI GdCNjQI ef KGfjI cJGH GdCUhd dEbdjOS hdjcf gPG BNQ GdcdGe hGdMeO ddg Ydi GdEJeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JTJed Ydi CTcGd gfOSjIs
(3hQO ai cTa GdXfhf L(B1 (3U` (B105 (3Cf CTcGd GdJCSjS ai GdgfOSI gh deDdaI TeS GdOjf eMeO HfCTQa GdSeQbfOi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeLGejYs